Exploring the role of microglia in mood disorders associated with experimental multiple sclerosis - Gentile, Antonietta; De Vito, Francesca; Fresegna, Diego; Musella, Alessandra; Buttari, Fabio; Bullitta, Silvia; Mandolesi, Georgia; Centonze, Diego (Frontiers in Cellular Neuroscience, 2015)
Microglia is increasingly recognized to play a crucial role in the pathogenesis of psychiatric diseases. In particular, microglia may be the cellular link between inflammation and behavioural alterations: by releasing a number of soluble factors, among which pro-inflammatory cytokines, they can regulate synaptic activity, thereby leading to perturbation of behaviour. In multiple sclerosis (MS), the most common neuroinflammatory disorder affecting young adults, microglia activation and dysfunction may account for mood symptoms, like depression and anxiety, that are often diagnosed in patients even in the absence of motor disability. Behavioural studies in experimental autoimmune encephalomyelitis (EAE), the animal model of MS, have shown that emotional changes occur early in the disease and in correlation to inflammatory mediator and neurotransmitter level alterations. However, such studies lack a full and comprehensive analysis of the role played by microglia in EAE-behavioural syndrome. We review the experimental studies addressing behavioural symptoms in EAE, and propose the study of neuron-glia interaction as a powerful but still poorly explored tool to investigate the burden of microglia in mood alterations associated to MS.